Hormonal interactions in the control of Arabidopsis hypocotyl elongation. - Collett, C; Harberd, N; Leyser, O (2000)
The Arabidopsis hypocotyl, together with hormone mutants and chemical inhibitors, was used to study the role of auxin in cell elongation and its possible interactions with ethylene and gibberellin. When wild-type Arabidopsis seedlings were grown on media containing a range of auxin concentrations, hypocotyl growth was inhibited. However, when axr1-12 and 35S-iaaL (which have reduced auxin response and levels, respectively) were grown in the same conditions, auxin was able to promote hypocotyl growth. In contrast, auxin does not promote hypocotyl growth of axr3-1, which has phenotypes that suggest an enhanced auxin response. These results are consistent with the hypothesis that auxin levels in the wild-type hypocotyl are optimal for elongation and that additional auxin is inhibitory. When ethylene responses were reduced using either the ethylene-resistant mutant etr1 or aminoethoxyvinylglycine, an inhibitor of ethylene synthesis, auxin responses were unchanged, indicating that auxin does not inhibit hypocotyl elongation through ethylene. To test for interactions between auxin and gibberellin, auxin mutants were grown on media containing gibberellin and gibberellin mutants were grown on media containing auxin. The responses were found to be the same as wild-type Arabidopsis seedlings in all cases. In addition, 1 microM of the auxin transport inhibitor 1-naphthylphthalmic acid does not alter the response of wild-type seedlings to gibberellin. Double mutants were made between gibberellin and auxin mutants and the phenotypes of these appear additive. These results indicate that auxin and gibberellin are acting independently in hypocotyl elongation. Thus auxin, ethylene, and gibberellin each regulate hypocotyl elongation independently.